Suburban policy mobilities: examining North American post-war engagements with Vällingby, Stockholm. Issue 4 (2nd October 2018) - Cook, Ian R.
ABSTRACT: This article calls for a detailed examination of the links between suburbia and the mobilization of policy knowledge. With suburbanization taking place across the world and the expanding literature on policy mobilities having little to say about the suburbs, this article begins to address this important gap in our collective understanding. It does this through a case study of Vällingby, a Stockholm suburb that captured the imagination of many planners and architects outside of Sweden during the 1950s and 1960s. Here the article considers the variegated ways in which planners and architects in North America engaged with Vällingby and used lessons learnt from Vällingby in their working practices. It focuses on the encounters with Vällingby by the New York-based architect Clarence Stein as well as those involved in the planning of the metropolitan Toronto suburb of Flemingdon Park. In so doing, the article demonstrates that suburbs are important sites within the circulation of policy knowledge and that audiences elsewhere engage with such sites in a multiplicity of ways. It also challenges a perception of the USA as an exporter and not an importer of suburban ideas and models.